(untitled) (American Journal of Human Psychology, 2024)
Emotional Styles and Social Intelligence are significant factors in maintaining a healthy well-being and good interpersonal relationships, which contribute to one’s mental health. Due to the changing circumstances, a decline in students’ mental health was evident. This study delves into the correlation between Emotional Styles and the Social Intelligence of university students, providing insights into how emotional well-being influences social relationships. A total of 375 university students participated, providing a diverse sample for a comprehensive investigation into these variables. The analyzed data revealed that the level of Emotional Styles is moderately evident among university students, emphasizing social intuition as the highest. On the other hand, there is a slightly high level of Social Intelligence, particularly the social information processing dimension. Pearson r analysis showed a positive correlation between the variables (p= <0.001; r=0.472). Furthermore, linear regression analysis highlights social intuition (p=0.041; t=2.049) and sensitivity to context (p=0.003; t=2.953) as significant predictors of Social Intelligence, emphasizing the importance of understanding nonverbal cues and contextual sensitivity in interpersonal interactions. With these results, the research recommends exploring additional factors, such as empathy and self-regulation, on the dimensions of Emotional Styles that could significantly influence Social Intelligence. Moreover, this research might consider increasing the sample size to include more diverse representations from the LGBTQ+ community in their demographic profile.